Relationships among the Microstructure, Mechanical Properties, and Fatigue Behavior in Thin Ti6Al4V - Y. Fan; W. Tian; Y. Guo; Z. Sun; J. Xu (Advances in Materials Science and Engineering)
The microstructures of Ti6Al4V are complex and strongly affect its mechanical properties and fatigue behavior. This paper investigates the role of microstructure on mechanical and fatigue properties of thin-section Ti6Al4V sheets, with the aim of reviewing the effects of microstructure on fatigue properties where suboptimal microstructures might result following heat treatment of assemblies that may not be suited to further annealing, for example, following laser welding. Samples of Ti6Al4V sheet were subjected to a range of heat treatments, including annealing and water quenching from temperatures ranging from 650°C to 1050°C. Micrographs of these samples were inspected for microstructure, and hardness, 0.2% proof stress, elongation, and fracture strength were measured and attributed back to microstructure. Fractography was used to support the findings from microstructure and mechanical analyses. The strength ranking from high to low for the microstructures of thin Ti6Al4V sheets observed in this study is as follows: acicular α′ martensite, Widmanstätten, bimodal, and equiaxed microstructure. The fatigue strength ranking from high to low is as follows: equiaxed, bimodal, Widmanstätten, and acicular α′ martensite microstructure.